(untitled) (Research, Society and Development, 2020)
Solidification/Stabilization (S/S) is an important technique used in waste treatment, due its low cost and easily processing. The aim of this study was to optimize and standardize the S/S process in a Brazilian company. The packing of the dangerous residue was done using a mixture of different solidifying agents, such as: clayey soil; superabsorbent polymer (SAP)/cellulose pulp (fluff) and sanding powder. It was evaluated the effect of different amount of solidifying agent over the volume of packed mixture, the final moisture and the cost of the S/S process, using a Central Composite Design. The results showed a minimum cost for the S/S operation of R 192.89/ton of liquid waste, using about 71.69 tons of clay soil for each ton of untreated residue, allowing a highly packed residue with a moisture up to 20% (w.b.).